2019
DOI: 10.1101/554626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating brain cell marker genes based on differential gene expression and co-expression

Abstract: 12Reliable identification of brain cell types is necessary for studying brain cell 13 biology. Many brain cell marker genes have been proposed, but their reliability 14 has not been fully validated. We evaluated 540 commonly-used marker genes 15 of astrocyte, microglia, neuron, and oligodendrocyte with six transcriptome and 16 proteome datasets from purified human and mouse brain cells (n=125). By 17 setting new criteria of cell-specific fold change, we identified 22 gold standard 18 marker genes (GSM) with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A comparison of the expression of brain markers 89 in animals from the control group and healthy brain samples 61 , sequenced on the same developmental day, confirmed that the tissue originated mainly from the brain ( Supplementary Fig. 1).…”
Section: Methodsmentioning
confidence: 58%
“…A comparison of the expression of brain markers 89 in animals from the control group and healthy brain samples 61 , sequenced on the same developmental day, confirmed that the tissue originated mainly from the brain ( Supplementary Fig. 1).…”
Section: Methodsmentioning
confidence: 58%